Lacutamab in patients (pts) with advanced mycosis fungoides (MF) according to KIR3DL2 expression: early results from the TELLOMAK phase 2 trial. (October 2021) - Bagot, Martine; Kim, Youn; Zinzani, Pier Luigi; Dalle, Stephane; Beylot-Barry, Marie; Ortiz-Romero, Pablo L; Cambalia, Andrea; Dereure, Olivier; Mortier, Laurent; Jacobsen, Eric; Battistella, Maxime; Gru, Alejandro; et al.
Abstract : Background: KIR3DL2 is a killer immunoglobulin-like receptor, expressed in >90% of Sézary syndrome (SS) pts and 50% in pts with MF. Lacutamab is a humanized first-in-class monoclonal antibody designed to deplete KIR3DL2-expressing cells via antibody-dependent cell-cytotoxicity and phagocytosis. In a previous phase 1 trial, lacutamab showed adequate safety profile with no dose limiting toxicities and a global response rate of 42.9% in pts with SS, with a median time to response of 4.9 months (m). Methods: TELLOMAK is an open-label, multi-cohort, international phase II trial. Up to 148 pts are planned to be enrolled. Pts are allocated to one of three cohorts: Cohort 1: SS, Cohort 2: KIR3DL2 expressing (≥1%) MF and Cohort 3: KIR3DL2 non-expressing MF, based on central KIR3DL2 testing. Eligible pts should have received at least 2 prior systemic therapies with no evidence of large cell transformation. Lacutamab 750 mg is administered as an intravenous (i.v.) infusion weekly × 5 weeks (w), every 2 w × 10 then every 4 w, until progression or unacceptable toxicity. The primary endpoint is global confirmed response, evaluated using the International Consensus Criteria. Secondary endpoints include safety, quality of life, other efficacy endpoints, and biomarker analysis. Evaluable pts should have at least one response assessment 5 w after treatment initiation. In each of the MF cohorts, the study follows a Simon 2-stage design in which 21 and 18 pts were required in stage 1 for Cohorts 2 and 3, respectively with early termination if <3 global confirmed responses per cohort were observed. Here we report early stage 1 data for the two MF cohorts. Results: As of January 20 2021, recruitment in stage 1 for both cohorts 2 and 3 is ongoing, with 12 pts enrolled in each cohort. Median age for all 24 pts is 57 years (range: 19–81). At study entry, 42% (n=5) and 17% (n=2) had stage III/IV in cohorts 2 and 3, respectively. Median number of prior systemic therapies is 3.5 (range: 2–10). At a median follow-up of 2.8 m (range: 0.3–14.1 m), 7 and 6 pts in cohort 2 and 3, respectively, are ongoing treatment. Overall, 19 pts were evaluable for response in Cohort 2 (n=11) and Cohort 3 (n=8). In Cohort 2, 5 skin responses were observed, of whom 3 had global confirmed responses (1 complete response, 2 partial responses). 7 pts had global stable disease. No responses are reported yet in Cohort 3. Adverse events (AEs) of any grade were observed in 17/24 pts (71%), of which 10/24 (42%) were treatment-related [TR]. Grade ≥3 AEs were observed in 2/24 (8%) pts, of which 1/24 (4%) was TR. Most common AEs were asthenia (N=6, 25%; TR: 2), pruritus (N=3, 12%; TR: 0), and peripheral oedema (N=2, 8%; TR: 1). Conclusion: Lacutamab met the predefined threshold of activity in the KIR3DL2 expressing MF cohort required to expand recruitment to 50 pts. Safety profile is reassuring and consistent with previous phase 1 data. Updated results on all stage 1 pts from cohort 2 and 3 will be presented.